Temperature, Labor Reallocation, and Industrial Production: Evidence from India - Jonathan Colmer (Institute of Labor Economics (IZA), 2021)
To what degree can labor reallocation mitigate the economic consequences of weather-driven agricultural productivity shocks? I estimate that temperature-driven reductions in the demand for agricultural labor in India are associated with increases in non-agricultural employment. This suggests that the ability of non-agricultural sectors to absorb workers may play a key role in attenuating the economic consequences of agricultural productivity shocks. Exploiting firm-level variation in the propensity to absorb workers, I estimate relative expansions in manufacturing output in more flexible labor markets. Estimates suggest that, in the absence of labor reallocation, local economic losses could be up to 69% higher.
Keywords: temperature; labor; reallocation; industrial; production; 330; temperature; labor reallocation; industrial production